Secondary Aortic Dissection after Endoluminal Treatment of an Intramural Hematoma of the Thoracoabdominal Aorta: Endovascular Extension with Two Stent Grafts and Scarce Distal Landing - Peter I. Kalmar; Peter Oberwalder; Peter Schedlbauer; Jürgen Steiner; Rupert H. Portugaller (Case Reports in Medicine)
Secondary dissection in the descending aorta after endovascular therapy may demand subsequent interventional procedures. This can set a particularly significant challenge for the endovascular specialist. When implanting an aortic prosthesis, a sufficient contact between the covered segment and the healthy vessel wall is advisable. However, our case shows that, in individual cases, it is indeed efficient to place an aortic stent graft on top of the distal end of the dissection. This is proven by a three-year follow-up CT-angiography.